Sales Salvador, Dora. Bridges over the world. Culture, translation and literary form in the transculturation narratives of José María Arguedas and Vikram Chandra. Bern: Peter Lang, Hispanic Perspectives Collection, 2004, 677 pp. - Pinilla Cisneros, Carmen María (2009)
The review does not present a summary.